Peningkatan Kualitas Jasa Menggunakan Metode Quality Function Deployment (QFD) Di Laundry Himalaya Colomadu - Rifa'i, Agus, Hafidh Munawir, ST, M.Eng (2017)
As a service provider, Laundry Himalaya attempting to improve the quality of service that has been the cause of termination of the contract of cooperation. This research purpose to measure the quality of service that has been given by the method of Service Quality (Serqual) and choose a solution by using Quality Function Deploymnet (QFD) to know the desire from the customer. In the Serqual there are 5 dimensions to measure the tangibles service, reliabity, assurance, responsiveness dam emphaty. The measurement of the services from 5 dimensions using gap 5 is compare perception and customer expectations. The measurement result with SERVQUAL method known to the customer is not satisfied with the value of the gap one -1,425 means necessary repairs. And processing in the QFD method on based on the HOQ there are 17 technical parameters as the improvement of the quality of solution. From 17 technical parameters connected with attributes in based on VOC to know the strong weak relationship that is then used to determine the priority of the improvements that will be in the aplly first. Based on the normalization contribution from 17 alternative that has the highest value will be done first improvement is add the service devision (9.3), conduct training ethics (9.2), invest the nature of the work ethos (8.6).